What is the Uncanny?. (28th August 2018) - Windsor, Mark
Abstract: I propose a definition of the uncanny: an anxious uncertainty about what is real caused by an apparent impossibility. First, I outline the relevance of the uncanny to art and aesthetics. Second, I disambiguate theoretical uses of 'uncanny' and establish the sense of the term that I am interested in—namely, an emotional state (a kind of anxiety) directed towards particular objects in the world which are characteristically eerie, creepy, and weird. Third, I look at Edgar Allan Poe's 'The Fall of the House of Usher' as a means of drawing out the conditions that I claim are essential to uncanny experiences, and then elaborate the terms of my proposed definition. Finally, I show how the definition accounts for two paradigmatic kinds of uncanny phenomena: cases of 'uncanny resemblances', which include twins, doppelgangers, and very lifelike representations of the human body; and unlikely coincidences of events.